2013
DOI: 10.1186/1475-2875-12-217
|View full text |Cite
|
Sign up to set email alerts
|

Severe malaria in Battambang Referral Hospital, an area of multidrug resistance in Western-Cambodia: a retrospective analysis of cases from 2006–2009

Abstract: BackgroundDespite recent malaria containment and control efforts leading to reduced incidence, Cambodia remains endemic for both Plasmodium vivax and multidrug-resistant Plasmodium falciparum malaria. Little has been reported in the peer-reviewed literature regarding the burden of severe malaria (SM) in Cambodia.MethodsMedical records for all patients admitted to the Battambang Referral Hospital (BRH) with an admitting or discharge diagnosis of SM from 2006 to 2009 (suspected SM cases) were reviewed. Those mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Higher propensity to contract malaria infection in men has been a consistent observation from this study region [9,20,34,35,38,39]. Male preponderance in malaria population has also been reported from other places in India [44−46] and elsewhere [47,48]. In contrast, female predominance was found in vivax malaria in Papua, Indonesia [36].…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…Higher propensity to contract malaria infection in men has been a consistent observation from this study region [9,20,34,35,38,39]. Male preponderance in malaria population has also been reported from other places in India [44−46] and elsewhere [47,48]. In contrast, female predominance was found in vivax malaria in Papua, Indonesia [36].…”
Section: Baseline Characteristicssupporting
confidence: 86%
“…Wasnik et al noted that the cause of death were ARF, metabolic acidosis, aspiration pneumonia and circulatory failure. Case fatality rates in the other studies from Africa have shown a high mortality rate of 13-21% [14,15]. Artesunin components as combination therapy are the drug of choice as per WHO recommendations and can be easily administered with hardly any side effects [11].…”
Section: Discussionmentioning
confidence: 99%
“…These cases are not endemic to the US, but occur in individuals with a history of recent travel or residence in malaria endemic areas. Roughly 10% of US malaria cases are considered severe by the World Health Organization (WHO) criteria (2, 3), with the vast majority of these being caused by Plasmodium falciparum (4-7). Patients with severe malaria are at risk for life-threatening complications including: renal failure, acute respiratory distress syndrome (ARDS), severe hemolytic anemia, and cerebral malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with severe malaria are at risk for life-threatening complications including: renal failure, acute respiratory distress syndrome (ARDS), severe hemolytic anemia, and cerebral malaria. Among these, cerebral malaria is arguably the most dire, since it can present rapidly, often with minimal warning signs, and has a mortality rate of 15-30% with treatment and 100% when untreated (2, 4, 8-10). The only FDA-approved treatment for severe malaria in the United States is quinidine, a stereoisomer of quinine that once saw routine hospital use as a cardiac anti-arrhythmic medication (11, 12).…”
Section: Introductionmentioning
confidence: 99%